Elections in Latin America campaigns, voters, and institutions - Pallister, Kevin (Rowman & Littlefield, 2024)
"This book provides an overview of elections throughout Latin America, including formal electoral institutions, informal practices, and the behavior of voters and candidates. Drawing on a wide range of scholarly and primary sources, the book provides readers with a highly accessible look at how elections in Latin America work."